MANAJEMEN KOMUNIKASI BENCANA DALAM PENCEGAHAN KEBAKARAN LAHAN GAMBUT DI SUMATERA SELATAN - Adli; Karmila, Leti (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2022)
The communication process to prevent repeated land fires is carried out by conveying information about the impact of fires and their prevention. The disaster communication process and prevention scheme have been planned. However, peatland fires in South Sumatra are still recurring, so it is necessary to review the disaster communication steps that have been taken. Disaster communication management is always needed both in emergency and post-disaster conditions. This study aims to evaluate and describe disaster communication management in preventing peatland fires in South Sumatra. This study uses a qualitative method with an evaluative study approach. Collecting data was done using interviews, observations, and documentation studies. Data analysis in this study used an interactive analysis model. The results of this study indicate that the elements of disaster communication management used in efforts to prevent peatland fires in South Sumatra consist of planning, organizing, implementing, and evaluating.